Studi Perbandingan Pengajaran Reaksi Reduksi Oksidasi Antara Cara Perubahan Bilangan Oksidasi dengan Cara Setengah Reaksi terhadap Hasil Belajar Siswa Kelas XII IPA 1 dan XII IPA 2 - Fauziah Fauziah (Universitas Batanghari Jambi, 2021)
Oxidation-Reduction Reactions (Redox) are one of the hardest reactions to equalize, this means that it is hard to determine the suitable Reaction Coefficient. An easier and more logical train of thought is to remember that a Reduction and an Oxidation reaction happens simultaneously. A Redox Reaction has two methods in order to equalize, that which is by using the “Change in Oxidation Number” method or the “Half-Reaction (Ion-Electron)” method. The students’ skills in completing a Redox Reaction can be observed in the grades that they have achieved. This observation is intended to find out if there is a difference in students’ grades if you were to teach them about the equalization of Redox Reactions using either of these two methods (the “Change in Oxidation Number” method and the “Half-Reaction” method). The population in this observation consists of the students of Class XII IPA 1 and Class XII IPA 2 of SMAS PERTIWI Jambi that are studying Oxidation-Reduction Reactions. Sample members consist of the students of Class XII IPA 1 and the students of Class XII IPA 3 of SMAS Pertiwi Jambi. The measuring instrument used is a test that has fulfilled standards. Normality tests and Homogeneity tests of the sample in question has been done before the Hypothetical test was implemented. The average grades of students using the “Change in Oxidation Number” method and the “Half-Reaction” method is 11.75 and 10.8 respectively. The T-value of calculations is approximately 1.81 while the T-value of tables is approximately 2.00. With the Level of Significance being 0.05. From the data provided above, it can be concluded that there is no difference in student grades whether the “Change in Oxidation Numbers” method or the “Half-Reaction” method is used to equalize Redox Reactions in applicative aspects.